Antibacterial effects of mangrove ethanolic leaf extract against zoonotic fish pathogen Salmonella arizonae - Jomel S Limbago; Josette Sosas; Angelie A Gente; Parif Maderse; Marjorie M Rocamora; Dennis K Gomez (Journal of Fisheries, 2021)
The emergence of multiple drug-resistant pathogens, affecting aquaculture and public health, has put the spotlight on alternative medicine research. This study was conducted to evaluate the In vitro and In vivo antibacterial activity of mangrove ethanolic leaf extract (MLEE) against Salmonella arizonae isolated from Carassius auratus. In vitro, antimicrobial activity of 10 mangrove species and 13 commercial antibiotics were determined using the agar diffusion method. MLEE with the highest antimicrobial activity were subjected to qualitative phytochemical tests and bioassay experiments. In vivo antibacterial activity of MLEE was assessed using C. auratus intraperitoneally injected with S. arizonae. Results showed that Sonneratia alba has the highest antimicrobial activity against S. arizonae followed by Avicennia marina, A. officinalis, Sonneratia ovata, Rhizophora mucronata, Excoecaria agallocha, and Bruguiera cylindrica. However, bacterial isolate was resistant to A. rhumpiana, Scyphiphora hydrophyllacea, and Laguncularia racemosa.  Interestingly, S. alba has comparable antimicrobial activity with amoxicillin, trimethoprim, novobiocin, and cefixime. The activity of S. alba could be attributed to the presence of flavonoids, saponin, sterols, tannin, and terpenoids. Moreover, S. alba has reduced and delayed the onset of goldfish mortality infected with S. arizonae. Based on these findings, the S. alba MLEE, is a potential antimicrobial resource against S. arizonae.